Perinatal outcome after fetoscopic release of amniotic bands: a single‐center experience and review of the literature. (23rd September 2013) - Javadian, P.; Shamshirsaz, A. A.; Haeri, S.; Ruano, R.; Ramin, S. M.; Cass, D.; Olutoye, O. O.; Belfort, M. A.
ABSTRACT Objectives To present two successful cases of fetoscopic release of amniotic bands with umbilical cord involvement and provide a review of the literature on fetal intervention for amniotic band syndrome (ABS). Methods Two cases of ABS were considered in conjunction with a review of the literature. A total of 14 fetuses with ABS underwent fetoscopic intervention between 1965 and 2012. Two of the authors independently completed literature searches in PubMed, Ovid and MEDLINE for articles related to ABS. Results Among 14 cases of ABS (12 published and our own two), 57% and 7% were complicated by preterm premature rupture of membranes and spontaneous preterm birth, respectively. Overall, fetoscopic intervention preserved limb function in 50% (7/14) of cases. Three cases involved intraoperative complications including intra‐amniotic bleeding and uterine wall bleeding, and incomplete procedure due to ineffective equipment. Conclusion Fetoscopic release of amniotic bands with minimally invasive surgery may allow preservation of life and/or limb function in cases of ABS. The acceptable functional outcome in 50% of cases is reassuring, although more experience and further studies are needed to determine the selection criteria that will justify the risk of this invasive in‐utero therapy for ABS. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.